Neurophysiological prediction of neurological good and poor outcome in post‐anoxic coma. (1st August 2016) - Grippo, A.; Carrai, R.; Scarpino, M.; Spalletti, M.; Lanzo, G.; Cossu, C.; Peris, A.; Valente, S.; Amantini, A.
Abstract : Objective: Investigation of the utility of association between electroencephalogram (EEG) and somatosensory‐evoked potentials (SEPs) for the prediction of neurological outcome in comatose patients resuscitated after cardiac arrest (CA) treated with therapeutic hypothermia, according to different recording times after CA. Methods: Glasgow Coma Scale, EEG and SEPs performed at 12, 24 and 48–72 h after CA were assessed in 200 patients. Outcome was evaluated by Cerebral Performance Category 6 months after CA. Results: Within 12 h after CA, grade 1 EEG predicted good outcome and bilaterally absent (BA) SEPs predicted poor outcome. Because grade 1 EEG and BA‐SEPs were never found in the same patient, the recording of both EEG and SEPs allows us to correctly prognosticate a greater number of patients with respect to the use of a single test within 12 h after CA. At 48–72 h after CA, both grade 2 EEG and BA‐SEPs predicted poor outcome with FPR=0.0%. When these neurophysiological patterns are both present in the same patient, they confirm and strengthen their prognostic value, but because they also occurred independently in eight patients, poor outcome is predictable in a greater number of patients. Significance: The combination of EEG/SEP findings allows prediction of good and poor outcome (within 12 h after CA) and of poor outcome (after 48–72 h). Recording of EEG and SEPs in the same patients allows always an increase in the number of cases correctly classified, and an increase of the reliability of prognostication in a single patient due to concordance of patterns.